The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1063/1.5094911
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic relations for microscopic properties at the interface between solid substrates and dense fluids

Abstract: Local structure, thermodynamics, and phase behavior of asymmetric particle mixtures: Comparison between integral equation theories and simulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 81 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…At the nanoscale, surface effects become dominant owing to which the confined fluids start exhibiting unique physical, thermal, electrical and chemical characteristics that differ from the macroscale [8,9]. Various features of a nanochannel, such as its pore size, length, roughness and morphology, greatly influence the transport characteristics of the fluid [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…At the nanoscale, surface effects become dominant owing to which the confined fluids start exhibiting unique physical, thermal, electrical and chemical characteristics that differ from the macroscale [8,9]. Various features of a nanochannel, such as its pore size, length, roughness and morphology, greatly influence the transport characteristics of the fluid [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…78 Russo et al found that the viscosity enhancement in nanoconfinement becomes more prominent with an increasing hydrophilicity of the channel walls, although variations in local viscosity exist also in hydrophobic channels. 26 Furthermore, Markesteijn et al 34 showed that the viscosities of several water models in a planar nanochannel separated by 4.3 nm distance are in good agreement with viscosities of associated water models without any explicit boundaries. We therefore specified a channel height large enough that scale effect on viscosity is negligible.…”
Section: A Viscosity Calculationmentioning
confidence: 95%
“…This study further distinguishes itself in providing a meticulous viscosity characterization, which is mandatorily required in calculating slip lengths. Viscosity can be calculated from MD simulations using various methods, such as the Green-Kubo formalism, [20][21][22][23] Couette shear flow simulations, [23][24][25][26] periodic perturbation method, 24,27 Stokes-Einstein relation, 28,29 transient-time correlation function, 30 and reverse nonequilibrium method, 31,32 each with their strengths and limitations. Backer et al presented an alternative approach that is based on counterflowing Poiseuille flows without the use of explicit boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Comparison of our analytical results for ρ s,R/L with those from the Ornstein-Zernike integral equation calculation which is carried out by Zhou et al[9]. Note that the analytical calculation is performed with η tot =2 15 π.…”
mentioning
confidence: 89%
“…Recently, considerable attention has been attracted by confined fluid and their mixture, whose structures and phase behaviors are drastically different from the corresponding bulk system [1]. In such systems, interactions between fluid-pore and fluid-fluid lead usually to interesting phenomena including laying [2], wetting [3,4], capillary condensation [5] and so on. Actually, among various confining geometries, the semipermeable membrane (SPM) has particular importance due to its ability to model the natural biological membranes and synthetic membranes [6,7].…”
Section: Introductionmentioning
confidence: 99%